THU0621-HPR The Effectiveness of Scapular Stabilization Exercises in Patients with Subacromial Impingement Syndrome and Scapular Dyskinesis. (9th June 2015) - Yuksel, E.; Yesilyaprak, S.S.
Abstract : Background: Alterations of the normal position or any abnormal motion of the scapula during active motions of shoulder is termed Scapular Dyskinesis and considered important risk factors for developing shoulder impingement syndrome (1). Some studies reported that decreased activity of the serratus anterior and middle and lower trapezius muscles; increased activity of the upper trapezius muscle may adversely affect scapular positioning, including scapular dyskinesis (2). Shoulder exercises must integrate scapular stabilization techniques in order to keep the scapula in the proper position to prevent impingement (1). Objectives: The aim of the study was to investigate the effectiveness of the scapular stabilization exercises in comparison with a control therapy in patients with subacromial impingement syndrome and scapular dyskinesis. Methods: This study was carried out on 44 patients who have scapular dyskinesis and had been diagnosed as subacromial impingement syndrome (SIS) between April 2014 and November 2014. Before treatment all the patients were randomly assigned to two groups. Standard physiotherapy program (electrotherapy, ultrasound treatment, streching and strengthening exercises) were applied to the control group (n=22) and standard physiotherapy program with scapular stabilization exercises were applied to the experimental group (n=22). All the patients received 20 sessions of physiotherapy for five times per week. All patients were evaluated before and after the 4-week physiotherapy program. All patients were blinded to the treatment option. Main outcome measures were shoulder pain (visual analog scale; VAS), shoulder range of motion, muscle strength, Scapular Dyskinesis Test, Scapular Reposition Test, scapular upward rotation, perceived symptoms changes and upper extremity functionality with Shoulder Pain and Disability Index (SPADI). Results: Before treatment, demographic and anthropometric characteristics were similar in groups and there was no statistically difference between groups (p>0.05). The results showed that all measurements were improved statistically in both groups after treatment (p<0.05). When the measurements of groups which performed after treatment compared, the experiment group had a much better result in terms of shoulder pain relief, muscle strength, improvement in scapular dyskinesis, perceived symptoms changes and upper extremity functionality and determined a significant difference between groups (Pain: F=8.207, p=0.010; Lower trapezius: F=20.79, p=0.001; Middle trapez; F=5.78, p=0.021; Serratus anterior; F=7.642, p=0.008; Scapular dyskinesis: χ 2 =11.458, p=0.001; perceived symptoms changes: χ 2 =8.553, p=0.036; SPADI: F=5.38, p=0.025). Conclusions: There were significant improvements in both groups. However, scapular stabilization exercises in addition to standard physiotherapy program seems to augment the effects of physiotherapy program. Scapular stabilization exercises should be used for improvement in the presence of scapular dyskinesis in patients with SIS and scapular dyskinesis. References: Baskurt Z, Baskurt F, Gelecek N, Ozkan MH. The effectiveness of scapular stabilization exercise in the patients with subacromial impingement syndrome. J Back Musculoskelet Rehabil 2011;24(3): 173-179 Struyf F, Nijs J, Mollekens S, et al. Scapular-focused treatment in patients with shoulder impingement syndrome: a randomized clinical trial. Clin Rheumatol 2012;32:73–85. Disclosure of Interest: None declared